(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the stylistic challenges encountered in translation processes, focusing on the complex interplay between linguistic structures and cultural nuances. The study analyzes how translators manage stylistic elements, including tone, register, imagery, and rhetorical devices, in transferring meaning between languages. Exploring both theoretical foundations and practical applications, this study identifies key stylistic challenges that arise in the translation process, including the preservation of cultural references and genre-specific language patterns.